The Utility of 3D Left Atrial Volume and Mitral Flow Velocities as Guides for Acute Volume Resuscitation. (7th July 2015) - Santosa, Claudia M.; Rose, David D.; Fleming, Neal W.
Abstract : Left ventricular end-diastolic pressure (LVEDP) is the foundation of cardiac function assessment. Because of difficulties and risks associated with its direct measurement, correlates of LVEDP derived by pulmonary artery (PA) catheterization or transesophageal echocardiography (TEE) are commonly adopted. TEE has the advantage of being less invasive; however TEE-based estimation of LVEDP using correlates such as left ventricular end-diastolic volume (LVEDV) has technical difficulties that limit its clinical usefulness. Using intraoperative acute normovolemic hemodilution (ANH) as a controlled hemorrhagic model, we examined various mitral flow parameters and three-dimensional reconstructions of left atrial volume as surrogates of LVEDP. Our results demonstrate that peak E wave velocity and left atrial end-diastolic volume (LAEDV) correlated with known changes in intravascular volume associated with ANH. Although left atrial volumetric analysis was done offline in our study, recent advances in echocardiographic software may allow for continuous display and real-time calculation of LAEDV. Along with the ease and reproducibility of acquiring Doppler images of flow across the mitral valve, these two correlates of LVEDP may justify a more widespread use of TEE to optimize intraoperative fluid management. The clinical applicability of peak E wave velocity and LAEDV still needs to be validated during uncontrolled resuscitation.